Реалізація технології формування толерантності студентів соціальних педагогів у виховній роботі - Гутник, О. Є. (НТУ "ХПІ", 2011)
The article analyses technology of social teacher’s training, influence of educational work on the process of their tolerance formation. The author considers components of professional pedagogical training of social teachers.
Keywords: толерантність; толерантне ставлення; рівні толерантності; модель толерантності